Morphology and element doping effects: phosphorus-doped hollow polygonal g-C3N4 rods for visible light-driven CO2 reduction. (26th January 2022) - Wang, Wen-Feng; Qiu, Li-Qi; Chen, Kai-Hong; Li, Hong-Ru; Feng, Lie-Feng; He, Liang-Nian
Abstract : The phosphorus-doped hollow polygonal g-C3 N4 rods were prepared and applied to photocatalytic CO2 reduction reaction with [Co(bpy)3 ]Cl2 as co-catalyst, delivering a CO evolution rate up to 447.5 μmol g −1 h −1 with a selectivity ca . 96%. Abstract : Photocatalytic CO2 reduction to valuable chemicals, especially fuels, is considered as a promising strategy to mitigate CO2 accumulation and tackle the energy crisis, among which photocatalysis is vital to achieve efficient and selective reduction of CO2 . In this work, phosphorus-doped hollow polygonal g-C3 N4 rods were prepared through phosphoric acid assisted self-assembly under hydrothermal conditions and subsequent thermal polymerization using phosphoric acid as the phosphorus source and melamine as the nitrogen-rich precursor. The resulting phosphorus-doped hollow polygonal g-C3 N4 rods feature increased specific surface area, visible light absorption and photogenerated carrier separation and transfer efficiency according to the structure and photoelectric properties characterization. Coupled with an earth abundant metal-based complex, i.e. [Co(bpy)3 ]Cl2, as a co-catalyst, the phosphorus-doped hollow polygonal g-C3 N4 rods deliver a CO evolution rate of up to 447.5 μmol g −1 h −1 with a selectivity of ca. 96%, being much higher compared to the pristine g-C3 N4 (67.01 μmol g −1 h −1 with a selectivity of ca. 94%) resulting from the improved light harvesting and charge transfer to the co-catalyst. Remarkably, the phosphorus-doped hollow polygonal g-C3 N4 rods can be reused 6 times while retaining constant catalytic activity in the photoreduction reaction. This work presents new insights into photocatalytic CO2 reduction by developing non-metal doping and hollow structural designs for semiconductor photocatalysts.